2016
DOI: 10.1186/s13054-016-1327-0
|View full text |Cite
|
Sign up to set email alerts
|

Speckle tracking echocardiography in patients with septic shock: a case control study (SPECKSS)

Abstract: BackgroundSepsis-induced myocardial dysfunction is a well-recognized condition and confers worse outcomes in septic patients. Echocardiographic assessment by conventional parameters such as left ventricular ejection fraction (LVEF) is often affected by ongoing changes in preload and afterload conditions. Novel echocardiographic technologies such as speckle tracking echocardiography (STE) have evolved for direct assessment of the myocardial function. We investigate the measurement of myocardial strain by speckl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 20 publications
8
80
0
5
Order By: Relevance
“…Further, using this method, some studies showed reduced inter‐ and intra‐observer variability in assessing regional LV function . Additionally, compared to LVEF, STE is affected to a much lesser degree by changes of ventricular loading conditions, myocardial compliance, and afterload properties because it measures deformation directly …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, using this method, some studies showed reduced inter‐ and intra‐observer variability in assessing regional LV function . Additionally, compared to LVEF, STE is affected to a much lesser degree by changes of ventricular loading conditions, myocardial compliance, and afterload properties because it measures deformation directly …”
Section: Discussionmentioning
confidence: 99%
“…22 Additionally, compared to LVEF, STE is affected to a much lesser degree by changes of ventricular loading conditions, myocardial compliance, and afterload properties because it measures deformation directly. 23 As strain values are shown to reveal subclinical disease in different morbidities, it might also be useful in early detection of subclinical heart failure in anthracycline-treated patients. 17 Mavinkurve-Groothuis et al 24 showed that global myocardial strain and strain rate in asymptomatic survivors of childhood cancer were fibers are the most sensitive and vulnerable to myocardial disease.…”
Section: Discussionmentioning
confidence: 99%
“…The slope of the regional stretch-strain relationship measured from tissue Doppler imaging (TDI) can be used as a noninvasive index of the myocardial inotropic state, but cannot be used in patients with atrial arrhythmias or high heart rates with fusion of mitral inflow E and A waves [120]. Recently, non-invasive speckle tracking echocardiography (STE) allowed combined regional and global myocardial function assessment [123,124]. Global peak longitudinal strain (GLS), determined from STE, is a sensitive and feasible method, which overcomes many of the limitations of LVEF.…”
Section: Assessment Of Cardiac Contractilitymentioning
confidence: 99%
“…(16) A recent study using STE in patients on the ICU with septic shock concluded that it is capable of detecting significant LV impairment which was not detectable by conventional echocardiographic techniques and also that the ventricular dysfunction is reversible in patients who survive their episode of sepsis. (17) Total isovolaemic time measures global LV electromechanical dys-synchrony & this is both common and associated with an increased mortality. Echocardiographically guided re-synchronisation therapy may significantly improve cardiac output in patents with septic shock and severe heart failure requiring high doses of vasopressors.…”
Section: Echocardiographymentioning
confidence: 99%